Pengaruh Pengelolaan Keuangan Bank Perekonomian Rakyat Melalui Rasio LDR, NPL, dan BOPO Terhadap Kinerja Keuangan Yang Diukur Dengan ROA di Wilayah Kota Depok periode 2015-2023 - Hermono Fauzi; Cecep Taufiqurrahman (Publikasi Indonesia, 2025)
This study aims to analyze the effect of financial management in People’s Credit Banks (BPR) through Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), and Operating Expenses to Operating Income (BOPO) on financial performance as measured by Return on Assets (ROA) in BPRs located in Depok City during the 2015–2023 period. The research employs a quantitative approach using secondary data obtained from the Financial Services Authority (OJK) reports. The analysis was conducted using panel data regression with a fixed effect model to examine both partial and simultaneous effects of the independent variables on ROA. The results indicate that LDR has a positive and significant effect on ROA, while NPL and BOPO have a negative and significant effect on ROA. Simultaneously, all three variables significantly affect the financial performance of BPRs in Depok City. These findings highlight the importance of credit management, asset quality, and operational efficiency in improving BPR profitability.